8(t-3)+4t=6(2t+2)-8

Simple and best practice solution for 8(t-3)+4t=6(2t+2)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(t-3)+4t=6(2t+2)-8 equation:


Simplifying
8(t + -3) + 4t = 6(2t + 2) + -8

Reorder the terms:
8(-3 + t) + 4t = 6(2t + 2) + -8
(-3 * 8 + t * 8) + 4t = 6(2t + 2) + -8
(-24 + 8t) + 4t = 6(2t + 2) + -8

Combine like terms: 8t + 4t = 12t
-24 + 12t = 6(2t + 2) + -8

Reorder the terms:
-24 + 12t = 6(2 + 2t) + -8
-24 + 12t = (2 * 6 + 2t * 6) + -8
-24 + 12t = (12 + 12t) + -8

Reorder the terms:
-24 + 12t = 12 + -8 + 12t

Combine like terms: 12 + -8 = 4
-24 + 12t = 4 + 12t

Add '-12t' to each side of the equation.
-24 + 12t + -12t = 4 + 12t + -12t

Combine like terms: 12t + -12t = 0
-24 + 0 = 4 + 12t + -12t
-24 = 4 + 12t + -12t

Combine like terms: 12t + -12t = 0
-24 = 4 + 0
-24 = 4

Solving
-24 = 4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5.1(x+3)=20.4 | | 3+8(2k+1)=11+16k | | 9+-3(n-5)=30 | | 18x^2-12x-17=0 | | 8x-3=3x-17 | | 7y+3=-5y-9 | | 3x-8=2(3x-76) | | 17x+5=17x-5 | | Graphy=2x+1 | | -4(3x+9)+3x=6-4(x-3) | | -4x-6y=-18 | | 2piR=x | | 3/5n-4/5=1/5n | | 4(x^3-4X)=0 | | (7rs^2)(-3r^5s^4)= | | 1900-6p=-2(10n+7) | | 6=-12(10n+7) | | 7d-6=22 | | -2v=-6-4t | | A=2x-6 | | 1x+2x=79 | | 4t-8=t-5 | | 2x=5y-108 | | -5(x+3)-(9x-4)=x-5+3 | | x-10+2x-221+0.5x+5=180 | | z(z-3)+2(z+3)=18 | | 5h+4=4h+11 | | w(20w-73)=-63 | | 6(x^2+x-20)=0 | | 5n+43=-2(1-7n) | | 6y-8=4y+2 | | 7+7x=7+8x |

Equations solver categories